Investigation of the relationship between strength and dynamic balance performance in elite wrestlers - Tatlici, A.; Unlu, G.; Cakmakci, E.; Cakmakci, O. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Background. Wrestlers rely heavily on the abilities of strength and balance to ensure success. Although previous studies have investigated the effects of different training methods on the athletic performance of strength and balance, there are a limited number of studies aimed at examining the relationship between these two performances. Problem and Aim. The purpose of this study was to examine the association between the variables of dynamic balance and dynamic muscle strength (isokinetic strength of the knee extensors and flexors). Methods. Thirty elite wrestlers age range 17 to 25 participated in this study (age: 21.7±2.6 years, height: 176.2±5 cm, weight: 78.3±11.2 kg). Biodex Balance System (BBS, Biodex Medical Systems Inc., Shirley, NY) was used to test dynamic balance, and three index scores were recorded as an overall stability index (OSI), an anterior-posterior stability index (APSI), and a medial-lateral stability index (MLSI). Strength measurements were conducted using an isokinetic dynamometer (Cybex, Humac Norm 2004). Pearson correlation was performed to determine the relationships, and the significance level was set at p < 0.05. Results. No significant correlations were observed between the variables of postural balance and strength (p>0.05). Conclusions. The findings of this study support the hypothesis that dynamic balance and leg muscle (hamstring and quadriceps) strength are independent of each other.